A Translation Shift Of Verbs And Verb Phrases In Subtitling The Adventure Of Tintin (2011) Movie - Wijanarko, Septian Bagas; , Dra. Dwi Haryati, M. Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research is descriptive qualitative research. The objectives of the research are to classify translation analysis shift of verbs and verb phrases and the equivalence of translation found in The Adventure of Tintin 2011 movie. The data in this research is English and Indonesian movie subtitle. The data source is in The Adventure of Tintin 2011 movie subtitle containing verbs and verb phrase. The writer uses documentation as the method of collecting the data in this research. The result of the research shows that: First, the writer finds two kinds of translation shift; they are the translation shift of verb and the translation shift of verb phrase. The translation shift can be classified into two types, category shift and level shift. The first part is translation shift of verb. In category shift, there are verb is translated into noun, verb into adverb, linking verb into adverb, and verb into verb+nya. In level shift, there are verb is translated into verb phrase and verb into yang + verb. Next, the second part is the translation shift of verb phrase. In the level shift the writer finds translation shift of verb phrase into verb, verb phrase into adjective, verb phrase into adverb, verb phrase into preposition, and verb phrase into verb imperative. Second, the equivalence of translation is classified into two types, equivalence and non equivalence. There are 275 data from 284 data or 97% of equivalence translation. Besides, the writer finds 9 data or 3% of 284 data of non equivalence translation.